2022
DOI: 10.20870/oeno-one.2022.56.2.4917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contrasting soils in a high-altitude vineyard of <i>Vitis vinifera</i> L. cv. Malbec: root morphology and distribution, vegetative and reproductive expressions, and berry skin phenolics

Abstract: The high-altitude viticulture of Mendoza is being increasingly recognised among the top wine regions worldwide. High levels of solar ultraviolet-B (UV-B) radiation, alluvial heterogeneous soils and cool night temperatures are major influences on Vitis vinifera L. phenotypic characteristics, especially on Malbec, Argentina’s emblematic grapevine variety. In the present work, the effect of intra-vineyard contrasting soil depth on Malbec was evaluated in a high-altitude vineyard (1450 m a.s.l.), over two growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Normally, poor soils such as those analyzed in GUA contribute to more stressful conditions that trigger the synthesis of some phenolic compounds. This GI has very heterogeneous soils with some difficulty in defining horizons, being a short soil that makes it more frequently exposed to water stress, contributing to the increase of phenolic compounds content according to Mezzatesta et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, poor soils such as those analyzed in GUA contribute to more stressful conditions that trigger the synthesis of some phenolic compounds. This GI has very heterogeneous soils with some difficulty in defining horizons, being a short soil that makes it more frequently exposed to water stress, contributing to the increase of phenolic compounds content according to Mezzatesta et al…”
Section: Resultsmentioning
confidence: 99%
“…37 Normally, poor soils such as those analyzed in GUA contribute to more stressful conditions that trigger the synthesis of some phenolic compounds. This GI has very heterogeneous soils with some difficulty in defining horizons, being a short soil that makes it more frequently exposed to water stress, contributing to the increase of phenolic compounds content according to Mezzatesta et al 38 The results of the anthocyanin profiles showed some individual anthocyanins associated with different GIs (Figure 1a). Many anthocyanins were higher in GUA, compared to the rest of the GIs (Table 1).…”
Section: Anthocyanins and Non-anthocyanins Profiles Table 1 Presents ...mentioning
confidence: 89%
“…Noble had shallow roots, with approximately 35% of the total roots in the 0-15 cm depth whereas most of the roots of Dogridge occurred in the 90-105 cm soil profile. Mezzatesta et al [51] indicated that root depth was not limited by soil conditions, but the distribution of fine roots was uneven in areas with more silt, clay, and organic matter in shallow soil. More roots distribution in shallow soil led to reduced plant growth, shorter ripening time, and smaller berries and fruit yield compared to deep soil.We found that new root production by 140 Ruggeri occurred in the 0-52 cm layer with the greatest root numbers between 10-30 cm.…”
Section: Influence Of Genotype On Grapevine Root Distributionmentioning
confidence: 99%